Probable fluoxetine-induced hepatomegaly: a case report - Braich, Jarnail S.; Sharma, Amiya; Vasistha, Harsh (International Journal of Basic & Clinical Pharmacology, 2023)
Depressive disorder is a common behavioural, psychiatric disorder. Among various antidepressants selective serotonin reuptake inhibitors (SSRIs) are preferred drugs for the treatment of depression. When second-generation antidepressants SSRIs and serotonin-norepinephrine reuptake inhibitors (SNRIs) are used to treat depression, 0.5–1% of patients develop mildly altered liver function without any symptoms. Various degrees of organ dysfunction are linked with drug-induced liver injury, which is unpredictable and might result from exposure to a drug. We reported suspected fluoxetine-induced hepatomegaly secondary to nine weeks of treatment with an SSRI fluoxetine. Upon cessation of the agent, the patient recovered symptomatically. The evidence is vital that the hepatomegaly in this patient was caused by fluoxetine.